PENGARUH TERAPI MUROTTAL SURAH AR-RAHMAN IRAMA JIHARKAH TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI DI UPT GADING REJO - Purwono, Janu; Sari, Rita (Coping: Community of Publishing in Nursing; Vol 11 No 5 (2023): Oktober 2023, 2023)
The prevalence of hypertension sufferers in the world and Indonesia is increasing. Various factors related to genetics and lifestyle such as lack of physical activity, intake of salty and fat-rich foods as well as smoking and drinking habits play a role in soaring hypertension rates. One of the complementary therapies that can control blood pressure is murottal surah Ar-Rahman therapy. The aim of the research was to determine the effect of murottal therapy of surah Ar-Rahman with the jiharkah rhythm on changes in blood pressure in hypertension sufferers in the working area of ??the UPT Puskesmas Gading Rejo Pringsewu Lampung. Quantitative research design with a quasi-experimental method with a one group pretest and posttest design without a control group. The research population was hypertension sufferers at the UPT Puskesmas Gading Rejo in September 2023. The total sample was 70 respondents using the purposive sampling method. Analysis used a paired test on systolic blood pressure and the Wilcoxon test on diastolic blood pressure. The results of statistical tests using the paired t test showed that the p-value of systolic blood pressure before and after murottal therapy of surah Ar-Rahman was 0,002 and the results of the Wilcoxon test of diastolic blood pressure before and after murottal therapy of surah Ar-Rahman obtained a p-value is 0,000. In conclusion, there is an effect of murottal therapy of surah Ar-Rahman with jiharkah rhythm on blood pressure before and after intervention is given to hypertension sufferers, so that murottal therapy of surah Ar-Rahman with jiharkah rhythm is effective for lowering blood pressure in hypertension sufferers.